Anaesthetic management of a dog with a lung laceration: novel use of an oxygen fuel cell. Issue 3 (7th August 2020) - Ward, Rob; Taylor, Polly M
Abstract : A one‐year‐old male entire Bracco Italiano weighing 29.4 kg presented with a pyothorax secondary to a thoracic foreign body. During the procedure the patient became hypotensive, which stabilised after intervention. After closing the thoracic cavity, negative pressure could not be obtained through the thoracic drain. An oxygen fuel cell was used to quickly and non‐invasively determine that a lung laceration was the source of the pneumothorax. The declining physiological condition of the patient during anaesthesia led to the decision to attach a one‐way valve to the chest drain, and for recovery to position the dog in lateral recumbency with the affected lung on the dependent side. The recovery was uneventful.